Sick or Unemployed? Examining Transitions into Sickness Insurance at Unemployment Benefit Exhaustion - Pierre Koning; Roger Prudon (Institute of Labor Economics (IZA), 2025)
Spikes in exits at unemployment insurance (UI) benefit exhaustion into other benefit schemes such as sickness insurance (SI) are well-documented. These spikes could be driven by relatively healthy workers maximizing their total duration of benefit receipt, or workers in ill health who remain on UI while incapable of working. While the first explanation calls for a stricter SI and UI system, the second highlights the need for increased information provision. We study the importance of these explanations by first documenting a spike in exits into SI at UI benefit exhaustion in the Netherlands. Comparing detailed health and labor market characteristics of exit cohorts, we show that the spike is unlikely to be driven by maximizing behavior of relatively healthy workers. Instead, our results point to catch-up of initial non-take-up of SI by workers with substantial mental and physical health conditions. This opposes earlier work on substitution between UI and SI/DI.
Keywords: H53; H75; J65; 330; sickness benefits; unemployment Insurance; spikes; non-take-up